Exploring Malaysian parents' and teachers' cultural conceptualization of adolescent social and emotional competencies: A qualitative formative study - Abd Hadi, Nur Hazwani; Midin, Marhani; Tong, Seng Fah; Chan, Lai Fong; Mohd Salleh Sahimi, Hajar; Ahmad Badayai, Abdul Rahman; Adilun, Norsinar (Frontiers in Public Health, 2023)
Introduction Global implementation of social and emotional learning (SEL) has been suggested to incorporate a systematic cultural adaptation process which relies on ground-up empirical data of a target cultural group in tailoring a culturally sensitive SEL intervention. Preliminary formative studies among local parents and educators were done to explore the conceptualization of social and emotional competencies (SECs) in various cultural settings, such as the continent of Africa and among the indigenous and refugee groups. Unfortunately, little scholarship has been devoted to studying the SEL adaptation process in Southeast Asian regions. This formative study aimed to explore Malaysian parents' and teachers' cultural conceptualization of adolescent SECs. Methods This qualitative study interviewed 12 Malaysian parents and 10 Malaysian teachers comprising of Malay (82%), Chinese (9%) and Indian (9%) races in an online focus group discussion. Sampling is purposive to parents of adolescents and teachers at secondary school only. Data were analyzed thematically to determine the culturally sensitive SEL constructs for Malaysian adolescents. Results All themes and sub-themes of SEC regarded as crucial for Malaysian adolescents are aligned with CASEL's five domains of competencies. Our findings extended the conceptualization of subskills under CASEL's relationship skills and responsible decision-making domains, which reflect Asian cultural values. The main themes of social competency: (a) preserving interpersonal relationships, (b) utilizing intrapersonal skills, and (c) communicating effectively, are shared with the established CASEL constructs. However, the underlying subthemes denote the unique cultural manifestation of social competency in Malaysia. Two of the emotional competency themes represent the established CASEL constructs: (a) practicing self-regulation, (b) demonstrating help-seeking behavior, and the other two themes signify Asian values: (c) upholding altruism, and (d) maintaining cultural display rules. Discussions This formative study revealed the habitual use of experiential and expressive suppressions as adaptive emotion regulation strategies in Malaysian collectivist culture and offered a potential alternative emotion regulation pathway suitable for Malaysian adolescents. It also informed the feasibility of implementing SEL modules developed based on the CASEL framework in Malaysia and suggested two key lessons to enhance the cultural sensitivity of SEL in Malaysia: effective, respectful communication and expressive writing.